THE MOST COMMON PROFESSIONAL QUALITIES OF A MODERN ENGINEER (The Conference Hub, 2025)
In addition to the knowledge acquired during education, a graduate of technical specialties must also possess certain spiritual qualities that are currently being formed in the educational process at universities. The discussion is based on the formation of the most general professional qualities of a modern engineer: competence, responsibility, diligence, independence, initiative, purposefulness, and the like.